2005
DOI: 10.1128/iai.73.8.5152-5159.2005
|View full text |Cite
|
Sign up to set email alerts
|

LcrV Plague Vaccine with Altered Immunomodulatory Properties

Abstract: Yersinia pestis, the causative agent of plague, secretes LcrV (low-calcium-response V or V antigen) during infection. LcrV triggers the release of interleukin 10 (IL-10) by host immune cells and suppresses proinflammatory cytokines such as tumor necrosis factor alpha and gamma interferon as well as innate defense mechanisms required to combat the pathogenesis of plague. Although immunization of animals with LcrV elicits protective immunity, the associated suppression of host defense mechanisms may preclude the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 47 publications
6
135
1
Order By: Relevance
“…Other mechanisms used by Y. pestis can also disturb the host immune responses; for example, it has been shown that the effectors YopP/YopJ of T3SS can be injected into endothelial cells and reduce the expression of adhesion molecules (ICAM-1 and E-selectin) on endothelial and bronchial epithelial cells, inhibiting the recruitment of PMNs to the infection site [47,48]. In addition to YopP, LcrV also inhibits neutrophil chemotaxis in vivo and in vitro [49].…”
Section: Negative Effects On the Activation Of Innate Cellular Districtmentioning
confidence: 99%
“…Other mechanisms used by Y. pestis can also disturb the host immune responses; for example, it has been shown that the effectors YopP/YopJ of T3SS can be injected into endothelial cells and reduce the expression of adhesion molecules (ICAM-1 and E-selectin) on endothelial and bronchial epithelial cells, inhibiting the recruitment of PMNs to the infection site [47,48]. In addition to YopP, LcrV also inhibits neutrophil chemotaxis in vivo and in vitro [49].…”
Section: Negative Effects On the Activation Of Innate Cellular Districtmentioning
confidence: 99%
“…Therefore, SpoT is sufficient to elicit a posttranscriptional mechanism that induces the expression of Y. pestis virulence factors directly or indirectly. Specifically, ppGpp induces the expression of three T3SS effectors: YopE and YopH, effectors that disrupt the host cell cytoskeleton and facilitate the resistance of phagocytosis (157,183,190), and LcrV, a factor that triggers interleukin-10 (IL-10) release and suppresses the proinflammatory cytokines tumor necrosis factor alpha (TNF-␣) and gamma interferon (IFN-␥) (142,150). As predicted, IL-10 levels in sera of mice inoculated with relA spoT mutants were diminished compared to those in the sera of mice inoculated with the WT.…”
Section: Yersinia Pestismentioning
confidence: 99%
“…Evidence of the interaction of V antigen with human TLR2 has been provided (34)(35). Overheim et al (35) showed that LcrV derived from Y. pestis and purified fromE. coli induced IL-I 0 from murine macrophages and human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects would depend on TLR2 stimulation (33). Evidence of the interaction of V antigen with human TLR2 has been provided (34)(35). Overheim et al (35) showed that LcrV derived from Y. pestis and purified fromE.…”
Section: Discussionmentioning
confidence: 99%